Accessibility, usability, and usefulness of a Web-based clinical decision support tool to enhance provider–patient communication around Self-management TO Prevent (STOP) Stroke. (December 2014) - Anderson, Jane A; Godwin, Kyler M; Saleem, Jason J; Russell, Scott; Robinson, Joshua J; Kimmel, Barbara
This article reports redesign strategies identified to create a Web-based user-interface for the Self-management TO Prevent (STOP) Stroke Tool. Members of a Stroke Quality Improvement Network (N = 12) viewed a visualization video of a proposed prototype and provided feedback on implementation barriers/facilitators. Stroke-care providers (N = 10) tested the Web-based prototype in think-aloud sessions of simulated clinic visits. Participants' dialogues were coded into themes. Access to comprehensive information and the automated features/systematized processes were the primary accessibility and usability facilitator themes. The need for training, time to complete the tool, and computer-centric care were identified as possible usability barriers. Patient accountability, reminders for best practice, goal-focused care, and communication/counseling themes indicate that the STOP Stroke Tool supports the paradigm of patient-centered care. The STOP Stroke Tool was found to prompt clinicians on secondary stroke-prevention clinical-practice guidelines, facilitate comprehensive documentation of evidence-based care, and support clinicians in providing patient-centered care through the shared decision-making process that occurred while using the action-planning/goal-setting feature of the tool.